2021
DOI: 10.1186/s10020-021-00346-8
|View full text |Cite
|
Sign up to set email alerts
|

Depleting SOX2 improves ischemic stroke via lncRNA PVT1/microRNA-24-3p/STAT3 axis

Abstract: Objectives Studies have widely explored in the filed of ischemic stroke (IS) with their focus on transcription factors. However, few studies have pivoted on sex determining region Y-box 2 (SOX2) in IS. Thus, this study is launched to figure out the mechanisms of SOX2 in IS. Methods Rat middle cerebral artery occlusion (MCAO) was established as a stroke model. MCAO rats were injected with depleted SOX2 or long non-coding RNA plasmacytoma variant tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Serum miR-32-3p, miR-148b-3p, miR-151b, let-7e-5p, miR-23b-3p, miR-29b-3p, miR-186-5p, miR-30a-5p, miR-124-3p, miR-128-3p, miR-192-5p, miR-222, miR-17-5p, and miR-221-3p may serve as potential diagnostic biomarkers for IS [ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] ]. Depleting sex-determining region Y-box 2 (SOX2) enhanced IS by the PVT1/miR-24-3p/STAT3 axis [ 63 ]. miR-335-5p, let-7b-5p, miR-34a-5p, and miR-3622b-5p have been reported as therapeutic targets or diagnostic biomarkers regarding IS treatment [ [64] , [65] , [66] , [67] ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum miR-32-3p, miR-148b-3p, miR-151b, let-7e-5p, miR-23b-3p, miR-29b-3p, miR-186-5p, miR-30a-5p, miR-124-3p, miR-128-3p, miR-192-5p, miR-222, miR-17-5p, and miR-221-3p may serve as potential diagnostic biomarkers for IS [ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] ]. Depleting sex-determining region Y-box 2 (SOX2) enhanced IS by the PVT1/miR-24-3p/STAT3 axis [ 63 ]. miR-335-5p, let-7b-5p, miR-34a-5p, and miR-3622b-5p have been reported as therapeutic targets or diagnostic biomarkers regarding IS treatment [ [64] , [65] , [66] , [67] ].…”
Section: Discussionmentioning
confidence: 99%
“…STAT3, a relatively conserved member of the STATs family, transduces signal pathways for transcriptional regulation of cellular homeostasis, proliferation, inflammation, etc ( 14 ). Previous experiments have observed that STAT3 expression levels were increased in the rat brain regions ipsilateral to middle cerebral artery occlusion (MCAO) relative to the sham group ( 15 , 16 ). Moreover, Adly et al.…”
Section: Discussionmentioning
confidence: 99%
“…In lncRNA PVT1-inhibited MCAO rats, oxidative stress and neuron apoptosis were limited, and neurological impairments improved. In MCAO rats, the lncRNA PVT1 was activated by the sex-determining region Y-box 2 (SOX), sponged miR-24-3p, and regulated STAT3 expression [ 104 ].…”
Section: Roles Of Ncrnas In Ischemia Stroke-induced Oxidative Stressmentioning
confidence: 99%